2003
DOI: 10.3348/kjr.2003.4.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Focal Hepatic Lesions: Evaluation with Contrast-Enhanced Gray-Scale Harmonic US

Abstract: ObjectiveTo determine the findings of various focal hepatic lesions at contrast-enhanced gray-scale ultrasound (US) using a coded harmonic angio (CHA) technique and emphasizing lesion characterization.Materials and MethodsThe study involved 95 patients with 105 focal hepatic lesions, namely 51 hepatocellular carcinomas (HCCs), 22 metastases, 22 hemangiomas, four cases of focal nodular hyperplasia (FNH), and six nontumorous nodules. After the injection of a microbubble contrast agent (SH U 508A), gray-scale har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
10
2
2
Order By: Relevance
“…2 The CEUS appearance of HCC in the vascular or late phase has also been described for ADI 3,4 and other methods. [5][6][7] However, no report to date has described the differences between encapsulated and nonencapsulated HCC. Tanaka et al 8 reported that most HCC nodules in which a reticular enhancement pattern was observed in the parenchymal phase had a fibrous capsule or septa in a configuration similar to that of reticular enhancement.…”
Section: Discussionmentioning
confidence: 96%
“…2 The CEUS appearance of HCC in the vascular or late phase has also been described for ADI 3,4 and other methods. [5][6][7] However, no report to date has described the differences between encapsulated and nonencapsulated HCC. Tanaka et al 8 reported that most HCC nodules in which a reticular enhancement pattern was observed in the parenchymal phase had a fibrous capsule or septa in a configuration similar to that of reticular enhancement.…”
Section: Discussionmentioning
confidence: 96%
“…Among various gray scale harmonic imaging techniques recently developed to overcome the shortcomings of conventional harmonic imaging, CHA is the one that separates harmonic signals from tissue and those from contrast agents and boosts harmonic return from the latter, which suppresses not only fundamental but also harmonic signals from the background tissue. [14][15][16] Thus, CHA is specifically sensitive to signals from a contrast agent but without contrast-related artifacts. The resultant high sensitivity to a contrast agent provides a sufficient stimulated acoustic emission effect at a medium MI, whereas other gray scale harmonic techniques usually require a maximal MI to achieve that.…”
Section: A B C D E Fmentioning
confidence: 99%
“…The resultant high sensitivity to a contrast agent provides a sufficient stimulated acoustic emission effect at a medium MI, whereas other gray scale harmonic techniques usually require a maximal MI to achieve that. 12,16,27 Furthermore, because there is less destruction of microbubbles, a period of continuous scanning is possible. We performed all contrast-enhanced sonographic examinations with a combination of a short period of continuous scanning and intermittent acoustic emission imaging at the same medium MI (0.6-0.8).…”
Section: A B C D E Fmentioning
confidence: 99%
See 2 more Smart Citations